2017
DOI: 10.1093/ptep/ptx005
|View full text |Cite
|
Sign up to set email alerts
|

BPS boojums in ${\cal N}=2$ supersymmetric gauge theories I

Abstract: We study 1/4 Bogomol'nyi-Prasad-Sommerfield (BPS) composite solitons of vortex strings, domain walls and boojums in N = 2 supersymmetric Abelian gauge theories in four dimensions. We obtain solutions to the 1/4 BPS equations with the finite gauge coupling constant. To obtain numerical solutions for generic coupling constants, we construct globally correct approximate functions which allow us to easily find fixed points of gradient flow equations. We analytically/numerically confirm that the negative mass of a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(22 citation statements)
references
References 91 publications
(158 reference statements)
0
22
0
Order By: Relevance
“…Lastly, many similarities between domain walls and D-branes have been shown in the literature. For example, D1-D3-like configuration was found in [27][28][29][30][31][32][33][34][35][36]. Furthermore, the low-energy effective theory on domain walls was found to be similar to that on D-branes [37][38][39]46].…”
Section: Introductionmentioning
confidence: 82%
“…Lastly, many similarities between domain walls and D-branes have been shown in the literature. For example, D1-D3-like configuration was found in [27][28][29][30][31][32][33][34][35][36]. Furthermore, the low-energy effective theory on domain walls was found to be similar to that on D-branes [37][38][39]46].…”
Section: Introductionmentioning
confidence: 82%
“…Domain walls and domain wall webs are discussed in [5,6,7]. Other BPS objects and composite objects are discussed in [8,9,10,11,12,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…However, it is not straightforward task to give it when two or more topological solitons coexist. In [17], we provided a simple and systematic way to give suitable boundary conditions called the global approximations. We showed that the global approximation is useful not only to solve numerically the master equation but also to figure out the boojum mass exactly without any ambiguity, such as that discussed in [16].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work [17], we were oriented to solving the master equation and revealing real shape of the boojums. In contrast, in this paper we will focus on physical aspects of the boojums and expand our understanding of composite solitons further by using the developments of our previous work [17]. First we investigate a composite solution that a (semi-)local string vortex ends on a wall in a weak gauge coupling limit.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation